Comparative analysis of entrepreneurial growth strategies of two multinational conglomerates in emerging markets. (7th July 2010) - Culpan, Refik; Chinta, Ravi
Multinational companies (MNCs) from emerging economies have received increasing attention in recent years. We studied the entrepreneurial growth of two family-controlled MNCs, namely Tata Group in India and Sabanci Holding in Turkey and compared their growth patterns. Building on the resource-based view (RBV) of the firm, we developed a conceptual framework by which we demonstrated how core competencies of these two conglomerate companies have led to their competitive advantages. Finally, we concluded that the success factors in becoming a MNC from a local company in an emerging economy depend on strategic and visionary leadership, smooth succession of the founders, strong value system and business ethics, multiple paths for growth and the establishment of strategic alliances with western companies. This study not only advances our understanding of historical and entrepreneurial developments in multinationality of firms from emerging countries, but also provides insights for future research.